2009
DOI: 10.1074/jbc.m807286200
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Phospholipids Lose Their Procoagulant Properties When Incorporated into High Density Lipoproteins

Abstract: Blood coagulation involves a series of enzymatic protein complexes that assemble on the surface of anionic phospholipid. To investigate whether apolipoproteins affect coagulation reactions, they were included during the preparation of anionic phospholipid vesicles using a detergent solubilization-dialysis method. Apolipoprotein components of high density lipoproteins, especially apolipoprotein A-I, had a pronounced anticoagulant effect. The anionic phospholipids lost their procoagulant effect when the vesicle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 46 publications
5
55
0
Order By: Relevance
“…137, 138 Other modes of action that could explain the beneficial effects of HDLs on coagulation include a reduction in platelet-activating factor production by endothelial cells, 139 inhibition of thrombin-induced endothelial tissue factor expression, 140 suppression of the procoagulant activity of erythrocytes, 141 and inactivation of anionic phospholipids that are required to accommodate the prothrombinase complex. 142 Consistent with these findings proposing a protective function of HDLs against thrombosis, Naqvi et al observed an independent inverse correlation between HDL-C levels and ex vivo thrombus formation in humans. 143 Furthermore, flow-induced thrombus formation was diminished by reconstituted HDLs as determined by flow-chamber based assays.…”
Section: Anti-inflammatory Effectssupporting
confidence: 59%
“…137, 138 Other modes of action that could explain the beneficial effects of HDLs on coagulation include a reduction in platelet-activating factor production by endothelial cells, 139 inhibition of thrombin-induced endothelial tissue factor expression, 140 suppression of the procoagulant activity of erythrocytes, 141 and inactivation of anionic phospholipids that are required to accommodate the prothrombinase complex. 142 Consistent with these findings proposing a protective function of HDLs against thrombosis, Naqvi et al observed an independent inverse correlation between HDL-C levels and ex vivo thrombus formation in humans. 143 Furthermore, flow-induced thrombus formation was diminished by reconstituted HDLs as determined by flow-chamber based assays.…”
Section: Anti-inflammatory Effectssupporting
confidence: 59%
“…32 Other proposed mechanisms by which HDL may reduce the risk of atherothrombosis are increased activities of the anticoagulants activated protein C and protein S, 35 reduced synthesis of plateletactiving factor and tissue factor by endothelial cells, 36,37 and neutralization of procoagulatory anionic phospholipids. 38 …”
Section: Hdl and Protection Against Cardiovascular Diseasementioning
confidence: 99%
“…In addition, the expression of hApoA-I in apoE defi cient mice and in hApo(a)-transgenic mice yielded similar results (89)(90)(91). A reduction of atherosclerosis has been reproduced in various apoA-I gene thereby abolishing their pro-coagulant properties (70). Whether these anti-thrombotic effects apply to humans is unknown.…”
Section: Apoa-imentioning
confidence: 99%